Risoluzione equazioni
10x-8+14×-5=6-9x-5x 8x-4x+6=-x+14-3×+2
5+11x-3(2x+4)-3x=10x+9 3(x-2)+5(x+1)=-2(x+4)+5
4/5-x/3=2/15 3/2-x/7=3/4
Risoluzione equazioni
10x-8+14×-5=6-9x-5x 8x-4x+6=-x+14-3×+2
5+11x-3(2x+4)-3x=10x+9 3(x-2)+5(x+1)=-2(x+4)+5
4/5-x/3=2/15 3/2-x/7=3/4
Gli ultimi quattro....
5 + 11x - 3(2x+4) - 3x = 10x + 9
5 + 11x - 6x - 12 - 3x = 10x + 9
11x - 6x -3x -10x = -5 +12 + 9
-8x = -16
x = -2
-----------------------------------
3(x - 2) + 5(x + 1)=-2(x + 4) + 5
3x - 6 +5x +5 = -2x - 8 +5
3x + 5x +2x = 6 - 5 - 8 +5
10x = -2
x = - (1/5)
------------------------------------
4/5-x/3=2/15
(12 - 5x)/15 = 2/15
12 - 5x = 2
5x = + 12 - 2
5x = 10
x = 2
-------------------------------
3/2-x/7=3/4
(42 - 4x)/28 = 21/28
42 - 4x = 21
4x = -21 + 42
4x = 21
x = 21/4
I primi due
10·x - 8 + 14·x - 5 = 6 - 9·x - 5·x
24·x - 13 = 6 - 14·x
24·x + 14·x = 6 + 13
38·x = 19
x = 1/2
----------------------------------
8·x - 4·x + 6 = -x + 14 - 3·x + 2
4·x + 6 = 16 - 4·x
8·x = 10
x = 5/4